Demographic characteristics and association of serum Vitamin B12, ferritin and thyroid function with premature canities in Indian patients from an urban skin clinic of North India: A retrospective analysis of 71 cases - Sidharth Sonthalia; Adity Priya; Desmond J Tobin (Wolters Kluwer Medknow Publications, 2017)
Background: The incidence of self-reported premature hair graying (PHG) seems to be on the rise. PHG has a profound impact on the patient's quality of life. It remains an incompletely understood etiology with limited and modest treatment options. Aim: The evaluation of the demographic and clinical profile of patients with premature canities, and exploration of the association of this entity with certain systemic disorders suspected to be related to its etiology. Methods: Seventy-one cases of premature canities (onset noticed by patients before 25 years of age) presenting to an urban skin clinic in Gurugram, India, between September 2012 and September 2015 with this complaint were retrospectively analyzed. The patient records were retrieved that provided details of the onset, duration and pattern of involvement, history, and examination findings (scalp, cutis, and general physical). Since all these patients had been screened for anemia, thyroid disorder, fasting blood glucose, and Vitamin B12 levels at the time of presentation, these parameters were also available for analysis. Results: The mean age at onset of graying was 10.2 ± 3.6 years (range: 5-19 years), with an almost equal gender distribution. The earliest age of onset recorded was 5 years. A positive family history of PHG (at least one of the biological parents or siblings) was obtained in 64 (90.1%) of the cases. The temporal regions of the scalp (35.2%) were most commonly involved followed by the frontal region (18.3%). Hypovitaminosis B12 and hypothyroidism showed significant association with the disorder, whereas anemia, serum ferritin, and fasting blood glucose did not. Conclusion: The age of onset of hair graying can be as low as 5 years. Temporal and frontal areas are the most commonly involved sites. A strong family history, Vitamin B12 deficiency, and hypothyroidism are strongly associated with PHG. Larger case-control studies are mandated for discerning the correlation of these and other risk factors with PHG.